(untitled) ("Conference on Universal Science Research 2023", 2025)
Synthesis and practical application of modified thiogol olgamers are of great importance in many fields such as chemistry, materials science, electronics and medicine. By changing their various physical and chemical properties, it is possible to create new materials, technologies and production processes. Such algorithms provide innovative solutions in many industries and create new opportunities for us